Late Cenozoic tectono-geomorphologic evolution of the northern Tian Shan mountain range: Insight from U-Pb ages of detrital zircon grains from the Upper Oligocene-Quaternary sediments of the southern Junggar basin. (1st June 2020) - Jia, Yingying; Sun, Jimin; Lü, Lixing
Graphical abstract: Highlights: The intra-continental uplift initiated at 25–23 Ma in the northern Tian Shan mountain range. The Borohoro range underwent another episode of uplift at 12–9 Ma. The Middle-Late Miocene uplift occurred in the whole Tian Shan mountain range. Abstract: Being one of the largest intra-continental orogens of the world, the Tian Shan orogenic belt was uplifted to its present elevation due to the far-field effect of the India-Asia convergence. In this study, we performed a systematic study on the Upper Oligocene-Quaternary sedimentary rocks from the southern Junggar basin, including conglomerate clast counting and detrital zircon U-Pb dating, to reconstruct the Late Cenozoic uplift history of the northern Tian Shan mountain range. The new detrital zircon U-Pb data provide new constrains on the Late Cenozoic intra-continental deformation of the Borohoro range. The Yili-Central Tian Shan and North Tian Shan were the major sources for the Junggar basin during the Latest Cretaceous-Paleogene period. At that time, the Borohoro range was characterized by low topography and wide drainage pattern. As the uplift of the North Tian Shan commenced at ~25–23 Ma, the high topography of the northern Borohoro range blocked the transport of sediments from the Yili-Central Tian Shan to the north. The North Tian Shan became the primary provenance area of the southern Junggar basin. According to sedimentary provenance analysis and geomorphologic survey, we infer that the Yili-Central Tian Shan started to uplift at 12–9 Ma. Combined with previously published data, our results suggest that the Middle Miocene uplift event most likely occurred in both the hinterland and foreland regions along the whole Tian Shan mountain range.